Bracing for armageddon? - Clark, William R. (Oxford University Press, 2008)
Since September 11th, the threat of a bioterrorist attack--massive, lethal, and unpreventable--has hung in the air over America. Bracing for Armageddon? offers a vividly written primer for the general reader, shedding light on the science behind potential bioterrorist attacks and revealing what could happen, what is likely to happen, and what almost certainly will not happen